2021
DOI: 10.3389/fsoc.2021.734738
|View full text |Cite
|
Sign up to set email alerts
|

Delayed-Onset PTSD and Coping Strategies of Chinese College Students During the COVID-19 Pandemic

Abstract: Coronavirus disease 2019 (COVID-19) has become a pandemic, and many Chinese college students both in China and abroad were house-quarantined. This study aimed to investigate the prevalence and symptoms of delayed-onset post-traumatic stress disorder (PTSD) and coping strategies among Chinese overseas and domestic college students during this pandemic. A questionnaire was opportunistically distributed to Chinese college students studying both domestically and abroad six months after the COVID-19 outbreak. The q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…We found that stab injuries significantly increased in 2021, i.e., in the later phase of the pandemic and after most COVID-19-related measures had been lifted in Germany. This is congruent with studies demonstrating that several psychological effects occurring after crises (posttraumatic stress disorder, anxiety, fear, and anger) may only be observed with a certain delay ( 29 , 30 ). A study from Mexico showed that assault and battery numbers decreased in the beginning of the COVID-19 pandemic but increased again when national lockdowns were lifted ( 31 ).…”
Section: Discussionsupporting
confidence: 89%
“…We found that stab injuries significantly increased in 2021, i.e., in the later phase of the pandemic and after most COVID-19-related measures had been lifted in Germany. This is congruent with studies demonstrating that several psychological effects occurring after crises (posttraumatic stress disorder, anxiety, fear, and anger) may only be observed with a certain delay ( 29 , 30 ). A study from Mexico showed that assault and battery numbers decreased in the beginning of the COVID-19 pandemic but increased again when national lockdowns were lifted ( 31 ).…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, the students reacted and mobilized positive short-term strategies that should be reinforced in order to protect them from long-term psychological harm. Furthermore, these strategies help students to stay mentally healthy and mitigate delayed-onset post-traumatic stress disorder during the COVID-19 pandemic ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though the above data were from different samples, PTSD seemed to emerge at the initial stage of the pandemic, and its prevalence became even higher two years after the outbreak of the pandemic. Such a phenomenon can be explained by the delayed onset of the PTSD, which has been frequently reported in different populations [ 40 ], including university students in China during the COVID-19 pandemic [ 41 ]. Furthermore, a systematic review summarizing 88 studies found that the prevalence of PTSD was 22.6% after pandemics (e.g., sudden acute respiratory syndrome [SARS], COVID-19) across all populations, including healthcare workers, infected cases, and the general public [ 42 ].…”
Section: Discussionmentioning
confidence: 99%